Hubungan konsep diri dengan prestasi akademik mahasiswa keperawatan - Pambudi, Prabawati Setyo; Wijayanti, Diyan Yuli (Jurusan Keperawatan FIKES UNSOED, 2012)
All forms of belief, feeling, and judgment of individuals believed about him and process of social interaction with their surroundings. It’s influences academic achievement. Students with less self-concept will tend to lose motivation and interest, which in turn impact the academic achievement. This research to determine the relationship between self-concept with academic achievement among students who achieved School of Nursing Diponegoro University. This study used a non-experimental quantitative. A number of sampling are 65 respondents was collected by questioners. The results of chi square test was p-value = 0.001 so there was a correlation between self-concept and academic achievement. It means that if the self-concept is good, the academic achievement is also good. Otherwise, if the self-concept is less, so the academic achievement is also bad. Educational institutions should consider the self-concept of students in the learning process.